An experimental analysis on catalytic dry reforming of methane (CDRM) performance of Ni/SBA-15 system - Türkmen, Mustafa Olcay. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2020., 2020)
The main objective of this study is to design and develop an efficient Ni based and SBA-15 supported mono metallic catalyst in order to produce a high yield synthesis gas via catalytic dry reforming of methane. The priority was given to the inhibition of the coke deposition. In this context, first of all, the effect of the catalyst preparation & pre-treatment (i.e. impregnation technique, calcination and reduction temperatures) and reaction conditions (i.e. reaction temperature) was investigated on the reference catalyst, 10% Ni/SBA-15. Secondly, effect of the modifications (i.e. metal loadings as 7.5 and 15%, addition of CTAB and TMB to SBA-15, drying temperature) on the catalyst were investigated. During these tests, the activity and selectivity was determined in terms of CH4 and CO2 conversions, and of H2/CO ratio, respectively. The results of the performance tests suggested that the catalytic performance is highly dependent on the preparation route. It was seen that incipient wetness impregnation method favors catalytic performance in terms of both activity and selectivity. Additionally, higher calcination and reduction temperatures found to have a positive effect on the catalytic performance. Changing the metal loading (7.5 and 15%) led to an inverse impact in both activity and stability; whereas lower drying temperatures increased the catalytic activity and stability. Although modification of the SBA-15 by addition of CTAB and TMB enhanced the properties of the supporting material, Ni/CTAB_SBA-15 and Ni/TMB_SBA-15 catalysts showed lower reactant conversions with higher stabilities. Characterizations on the chosen samples indicated coke formation over the surface of the catalysts and the coke deposition could be suppressed with an appropriate preparation route. All in all, the results of the performance tests and characterization techniques suggested that 10% Ni/SBA-15 catalyst which was impregnated with the incipient wetness impregnation method and calcined at 750 °C for 6 hours with 2 °C/min ramping rate in air was the most promising CDRM catalyst. This idea was also supported by the stability test conducted at 750 °C for 72 hours.
Keywords: Methane.; Catalytic reforming.